"You are different and not mainstream": An Emotion-Based Case Study of Two South Asian English Language Learners. Issue 4 (2nd October 2019) - Rawal, Hima; De Costa, Peter I.
ABSTRACT: A limited ability to pursue postsecondary education often leaves English language learners (ELLs) with a gamut of negative emotional experiences. Using an emotionally oriented framework to guide our study, this article focuses on the experiences of two female South Asian students who graduated from different U.S. high schools. We explored what emotions they encountered during their college preparation process and what factors shaped such emotions. Findings from our in-depth interviews revealed that our participants encountered negative emotions such as worry, discouragement, indignation, envy, confusion, and intimidation that were related to their ELL identity. We also demonstrate that it is not only their limited proficiency in English that hinders the ELLs from attending four-year colleges but also their families' economic status, a lack of awareness of college preparation courses, and a lack of assistance with their test preparation that contribute to the emergence of negative emotions.